Modeling and correction analysis of regional ionospheric modeling - Ji, Yuanfa; Liu, Yu; Sun, Xiyan; Guo, Ning; Zhao, Songke; Kamarul Hawari, Ghazali (Institute of Electrical and Electronics Engineers Inc., 2022)
The Global Navigation Satellite System (GNSS), due to its all-weather lobal monitoring and high precision, makes it possible to use GNSS observation data to accurately extract the total electron content (TEC) of the ionosphere and to study ionospheric activities. At the same time, the delay error caused by the ionosphere to GNSS signals is also one of the main sources of error in GNSS positioning. For regional users, using as few stations as possible to establish an ionospheric TEC model within the region has higher efficiency and range practicability. This paper realizes the establishment of a regional ionospheric TEC model based on spherical harmonics, and establishes an ionospheric TEC model in the 15∼45°N and 105°∼135°E regions, which is compatible with IGS (International GNSS Service, IGS) and CAS (Chinese Academy of Sciences, CAS), the overall difference is more than 70% within ±3TECU.